2009
DOI: 10.2478/v10140-009-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender on outcome following coronary artery bypass grafting surgery

Abstract: Background. Women experience greater complications and early mortality after both percutaneous interventions and coronary bypass surgery (CABG). Coronary artery disease is becoming more prevalent among women. The aim of the study was to determine whether gender differences in outcomes of surgical treatment persist at our institution.Methods. A retrospective review of 3177 consecutive CABG patients operated on at our institution during a five-year period. A number of demographic and preoperative risk factors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the transanal approach [33], a Hill‐Ferguson retractor was inserted into the anal canal, and the anterior rectal wall was exposed. With a finger inserted in the vagina, the true borders of the rectocele were delineated.…”
Section: Methodsmentioning
confidence: 99%
“…In the transanal approach [33], a Hill‐Ferguson retractor was inserted into the anal canal, and the anterior rectal wall was exposed. With a finger inserted in the vagina, the true borders of the rectocele were delineated.…”
Section: Methodsmentioning
confidence: 99%
“…Samalavicius et al [16] found no significant differences in the incidence of stroke between male and female patients, although the rate was quite high for the women. In correlation with the literature, we found higher rates of cognitive function disorder and stroke in the females in our study, but these were not statistically significant (p= 0.242).…”
Section: Discussionmentioning
confidence: 93%